2009
DOI: 10.1038/ajg.2008.120
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Influenza Vaccine in Children With Inflammatory Bowel Disease

Abstract: OBJECTIVE Patients with inflammatory bowel disease (IBD) frequently receive immunosuppressive therapy. The immune response in these patients to vaccines has not been well studied. We conducted a prospective, open label study to evaluate the serologic response to influenza vaccine in children with IBD. METHODS Serum was obtained from 146 children and young adults with IBD (96 CD, 47 UC, 3 IC) for baseline influenza titer, immediately followed by immunization with trivalent [A/Solomon Islands/3/2006 (H1N1), A/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 31 publications
2
128
2
1
Order By: Relevance
“…However, when patients are receiving immunosuppressive therapies with combined thiopurines and anti-TNF agents, serologic responses to vaccines are impaired ( 22,23,(43)(44)(45)(46)(47)(48)(49)(50)(51). Nonetheless, even a blunted vaccination response is thought to be of benefi t ( 52 ) and thus recommendations for infl uenza vaccination with inactivated vaccine continue to be broadly applicable to all patients, regardless of immunosuppression status ( 13,53 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…However, when patients are receiving immunosuppressive therapies with combined thiopurines and anti-TNF agents, serologic responses to vaccines are impaired ( 22,23,(43)(44)(45)(46)(47)(48)(49)(50)(51). Nonetheless, even a blunted vaccination response is thought to be of benefi t ( 52 ) and thus recommendations for infl uenza vaccination with inactivated vaccine continue to be broadly applicable to all patients, regardless of immunosuppression status ( 13,53 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…87,88 For example, some studies have suggested that patients on TNF inhibitors may have a slightly decreased immune response to influenza vaccine. [89][90][91] Specific data for patients with IBD are very scarce. Some authors have evaluated the serological response to influenza vaccine in patients with IBD and observed that those receiving anti-TNF therapy were less likely to be seroprotected.…”
Section: What Factors Affect the Efficacy Of Hbv Vaccination In Ibd Pmentioning
confidence: 99%
“…Some authors have evaluated the serological response to influenza vaccine in patients with IBD and observed that those receiving anti-TNF therapy were less likely to be seroprotected. 90 Others have demonstrated a suboptimal response to pneumococcal vaccination in patients with IBD who are receiving combination therapy with immunosuppressants plus anti-TNF drugs. 92 In healthy individuals, several risk factors for nonresponse have been identified, including immunosuppressive disease, smoking, older age, male gender and high body mass index.…”
Section: What Factors Affect the Efficacy Of Hbv Vaccination In Ibd Pmentioning
confidence: 99%
“…Therefore, we were not able to discern differences in immunization uptake or adverse events in patients receiving immunosuppressive therapy. Although we did not have access to serologic immunity testing in our cohort, most studies have demonstrated adequate immunogenicity to most influenza strains, 24,33,34 and the reduced health services utilization in IBD patients compared with controls in the 6 months after administration suggests protection.…”
Section: Figurementioning
confidence: 99%